Extra‐Framework Aluminum‐Assisted Initial C−C Bond Formation in Methanol‐to‐Olefins Conversion on Zeolite H‐ZSM‐5. (18th July 2018) - Wang, Chao; Chu, Yueying; Xu, Jun; Wang, Qiang; Qi, Guodong; Gao, Pan; Zhou, Xue; Deng, Feng
Abstract: Surface methoxy species bound to an extra‐framework Al (SMS‐EFAL) was unambiguously identified by advanced 13 C‐{ 27 Al} double‐resonance solid‐state NMR technique in the methanol‐to‐olefins reaction on H‐ZSM‐5 zeolite. The high reactivity of the SMS‐EFAL leads to the formation of surface ethoxy species and ethanol as the key intermediates for ethene generation in the early reaction stage. A direct route for the initial C−C bond formation in ethene was proposed and corroborated by density functional theory calculations.